1999
DOI: 10.1590/s1516-35981999000400011
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do desempenho ao primeiro parto de fêmeas Nelore e F1

Abstract: RESUMO -O objetivo deste estudo foi comparar o desempenho ao primeiro parto de fêmeas Nelore e mestiças F1. Os dados usados são referentes a 741 partos de fêmeas Nelore e F1, nascidas do acasalamento de vacas Nelore com touros das raças Aberdeen Angus, Brangus (pelagens preta e vermelha), Canchim, Nelore, Gelbvieh e Simental, nascidas entre 1989 e 1993. As informações referentes a 566 bezerros nascidos entre 1991 e 1995, do acasalamento dessas fêmeas com touros Aberdeen Angus, Brangus, Nelore, Simental, Gelbvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
1
4
0
2
Order By: Relevance
“…Our AFC mean agrees with those reported by Pelicioni et al (1999) 2000) and Bertazzo et al (2004), studying Nelore cattle in the state of São Paulo, Brazil reported means of 41.7, 38.3 ± 3.5 and 38.7 ± 4.5 months, respectively, and for another zebu breed, Lôbo (1998) calculated a mean of 59 ± 16.4 months for the same trait. Smaller means are recorded European cattle (Frazier et al, 1999;Pelicioni et al, 1999) and in Nelore herds where dams had been prematurely exposed to sires (Pereira et al, 2002;Dias et al, 2004;Silva et al, 2005).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Our AFC mean agrees with those reported by Pelicioni et al (1999) 2000) and Bertazzo et al (2004), studying Nelore cattle in the state of São Paulo, Brazil reported means of 41.7, 38.3 ± 3.5 and 38.7 ± 4.5 months, respectively, and for another zebu breed, Lôbo (1998) calculated a mean of 59 ± 16.4 months for the same trait. Smaller means are recorded European cattle (Frazier et al, 1999;Pelicioni et al, 1999) and in Nelore herds where dams had been prematurely exposed to sires (Pereira et al, 2002;Dias et al, 2004;Silva et al, 2005).…”
Section: Resultssupporting
confidence: 91%
“…Smaller means are recorded European cattle (Frazier et al, 1999;Pelicioni et al, 1999) and in Nelore herds where dams had been prematurely exposed to sires (Pereira et al, 2002;Dias et al, 2004;Silva et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…A precocidade da raça Brangus em comparação à Nelore também foi observada por Pelicioni et al (1999), que compararam a idade ao primeiro parto de fêmeas Nelore e F1 de várias raças com Nelore, entre elas a Brangus, e observaram menor idade para os animais cruzados. A menor idade ao primeiro parto foi para os animais cruzados Nelore x Angus, seguidos pelo Nelore x Brangus.…”
Section: Coeficiente De Determinação (Coefficient Of Determination)unclassified
“…The highest price paid for F from the BX genetic group is related to its final destination for this category, since they are mainly acquired for replacement of cows, as the British breeds and their crosses with zebu breeds are considered to have fertility precocity and maternal ability compared with continental races (Pelicioni et al, 1999). In addition, the study area has a transition tendency to commercialized British breeds as breeding cows; this may be the reason that producers pay more for F compared with M calves.…”
Section: Resultsmentioning
confidence: 99%